The morphological study of the pelvic guirdle and hind limbs of Jardina Roof rat (Rattus rattus) - Youssef , Abdelgader K.; Badr , Fatma A.; Khalifa , Hanin A. (Scientific Journal of University of Benghazi, 2022)
The morphology of pelvic girdle and the hind limbs skeleton of Jardina roof rat were studied. The girdle has one pair of os-coxae, each os-coxae consisted of anterior-dorsal illium, posterior dorsal ischium and ventral posterior pubis. The construction of the bones is generally similar to other rodents. There were differences between the acetabulum, obturator, ischium and pubis of the jardina roof rat and African giant rat. The hind limbs are comprised of the single proximal bone, the femur and the distal paired bone, the tibia-fibula. The three trochanters of the femur were the same as other rats. The fibula was shorter than the tibia and separated proximally with a large interosseous space and fused with its distal third length to the tibia. The tarsals are the proximal bones that formed the ankle and the metatarsals are the distal bones that form the sole of the foot. The five metatarsals ended with three phalanges except the first one which has two phalanges. The fifth digit is characterized by an s-shaped phalanx.